Buffering brain aging: education moderates language impairment in Parkinson's disease - Kim, Minchul; Yoo, Kwangsun (Frontiers in Cellular Neuroscience, 2025)
BackgroundCognitive reserve (CR) refers to the discrepancy between brain pathology and observed cognitive decline. While education is a key indicator of CR, its role as a potential moderator in the relationships between brain morphology and cognitive impairments in Parkinson's disease (PD) remains unclear. This study examined whether education affects the relationship between brain age and cognitive impairments in patients with PD.MethodsData from 58 patients with PD were analyzed using a secondary dataset from the OpenNeuro database. Participants aged ≥55 years were on stable medications and underwent standardized neuropsychological assessments. Brain age predictions were generated from T1-weighted magnetic resonance imaging (MRI) using the brainageR package, and the brain age difference (BAD) was calculated after correction for regression dilution. The moderation effect of education on the relationship between BAD and cognition was assessed using Hayes' PROCESS macro. The primary outcome was cognitive performance across six domains: attention, executive function, language, learning and memory, visuospatial ability, and global cognition.ResultsAmong the six domains, a significant moderation effect of education was found only for language ability (β = 0.01, p = 0.013, R2 = 0.20). The relationship between BAD and language was steeper at lower education levels. No statistically significant moderation was found in the remaining five domains.ConclusionHaving more years of education is associated with buffering the effects of accelerated brain aging on language ability in PD.